A Case Report of Asymptomatic Covid-19 Infection Death in Gemelli Pregnancy - Soniasari, Soniasari; Fauziah, Munaya (Ahmad Dahlan Medical Journal, 2022)
We present the case of a 23-year-old woman, G1P0A0, Gemelli (twins) with a gestational age of 38 weeks. The patient was referred to a type C referral hospital with complaints of low back pain without other symptoms. Antigen Rapid Test Swab examination with positive results and nasopharyngeal and oropharyngeal swab sampling for Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) examination of patients gave positive results with asymptomatic infection (without symptoms). Gemelli's pregnancy, which is considered a high risk and COVID-19 infection in the patient, resulted in parturition being performed by Sectio Caesarea. Both babies were born alive, but the first baby died on the first day, followed by the second baby on the second day after birth and then the mother experienced a worsening of the condition, namely in a coma placed in the ICU, on the third postpartum day she experienced respiratory and cardiac arrest and was declared dead.